Durvalumab after definitive chemoradiotherapy in locally advanced unresectable non-small cell lung cancer (NSCLC): Real-world data on survival and safety from the German expanded-access program (EAP). (December 2020) - Faehling, Martin; Schumann, Christian; Christopoulos, Petros; Hoffknecht, Petra; Alt, Jürgen; Horn, Marlitt; Eisenmann, Stephan; Schlenska-Lange, Anke; Schütt, Philipp; Steger, Felix; Brückl, Wolfgang M.; Christoph, Daniel C.
Highlights: Durvalumab after chemoradiotherapy is safe and effective in clinical practice. Survival in the German EAP was similar to the PACIFIC trial. Patients with oligometastatic or autoimmune disease might benefit from durvalumab. PD-L1-negative and PD-L1 positive patients have similar survival. Abstract: Background: Following the PACIFIC trial, durvalumab has been approved by the European Medicines Agency (EMA) for consolidation of locally advanced PD-L1-positive NSCLC after chemoradiotherapy (CRT). Patients were treated with durvalumab in the EAP from 22.11.2017 to 15.10.2018 allowing analysis of its efficacy and safety. Methods: Data from 56 centres were analysed for adverse events (AE), progression-free survival (PFS), overall survival (OS). Results: 126 patients actually received at least 1 cycle durvalumab. Compared to the PACIFIC trial, the EAP population had more advanced stage and included "oligometastatic" stage IV patients and patients with autoimmune disease. PFS (20.1 months) and OS (not reached) were similar in the EAP and the PACIFIC trial. 42.9 % completed 12 months of durvalumab without deaths during FU. Stage IV patients (n = 7) had encouraging OS (not reached at 27 months). Autoimmune disease did not affect survival. PFS and OS were similar in PD-L1-negative patients (n = 32) and PD-L1-positive patients (n = 79). Conclusions: Survival in the EAP was comparable to the PACIFIC trial. Selected stage IV patients and patients with autoimmune disease may benefit from durvalumab consolidation and should be included in future immuno-oncological trials. PD-L1 did not predict survival challenging the exclusion of PD-L1-negative patients from durvalumab consolidation. In summary, durvalumab consolidation is safe and effective in a European real-world setting.